Intrafraction motion monitoring to determine PTV margins in early stage breast cancer patients receiving neoadjuvant partial breast SABR. (May 2021) - Mouawad, Matthew; Lailey, Owen; Poulsen, Per; O'Neil, Melissa; Brackstone, Muriel; Lock, Michael; Yaremko, Brian; Shmuilovich, Olga; Kornecki, Anat; Ben Nachum, Ilanit; Muscedere, Giulio; Lynn, Kalan; et al.
Highlights: Treating patients prone with SABR may be able to reduce treatment time to 1 or 3 fractions. Accounting for treatment error with a target margin is important. In this treatment scheme, it is unknown what target margin to use. We assessed intra-fraction motion and derived evidence-based target margins. Future work will be to develop immobilization devices to further improve treatment. Abstract: Background and purpose: To quantify intra-fraction tumor motion using imageguidance and implanted fiducial markers to determine if a 5 mm planning-target-volume (PTV) margin is sufficient for early stage breast cancer patients receiving neoadjuvant stereotactic ablative radiotherapy (SABR). Materials and methods: A HydroMark© (Mammotome) fiducial was implanted at the time of biopsy adjacent to the tumor. Sixty-one patients with 62 tumours were treated prone using a 5 mm PTV margin. Motion was quantified using two methods (separate patient groups): 1) difference in 3D fiducial position pre- and post-treatment cone-beam CTs (CBCTs) in 18 patients receiving 21 Gy/1fraction (fx); 2) acquiring 2D triggered-kVimages to quantify 3D intra-fraction motion using a 2D-to-3D estimation method for 44 tumours receiving 21 Gy/1fx ( n  = 22) or 30 Gy/3fx ( n  = 22). For 2), motion was quantified by calculating the magnitude of intra-fraction positional deviation from the pretreatment CBCT. PTV margins were derived using van Herkian analysis. Results: The average ± standard deviation magnitude of motion across patients was 1.3 ± 1.15 mm Left/Right (L/R), 1.0 ± 0.9 mm Inferiorly/Superiorly (I/S), and 1.8 ± 1.5 mm Anteriorly/Posteriorly (A/P). 85/105 (81%) treatment fractions had dominant anterior motion. 6/62patients (9.7%) had mean intra-fraction motion during any fraction > 5 mm in any direction, with 4 in the anterior direction. Estimated PTV margins for single and three-fx patients in the L/R, I/S, and A/P directions were 6.0x4.1x5.9 mm and 4.5x2.9x4.3 mm, respectively. Conclusion: Our results suggest that a 5 mm PTV margin is sufficient for the I/S and A/P directions if a lateral kV image is acquired immediately before treatment. For the L/R direction, either further immobilization or a larger margin is required.